PERENCANAAN DAN PERANCANGAN CHILDREN CENTER DENGAN PENDEKATAN PERILAKU DI DENPASAR BARAT: Bahasa Indonesia - Ni Wayan Dewi Widyawati; Made Suryanatha Prabawa; I Ketut Sugihantara; Putri Ayu Devy Permata Sari (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2024)
Early childhood is a group of children who experience a development process that has unique characteristics, including aspects of physical growth and development, intelligence, communication and social-emotional abilities. In general, each stage of a child's development has the same development pattern, but with different developmental achievements. Education for early childhood is very important to support children's development during the golden age. Apart from that, the large number of parents who are busy working is also the main reason why the existence of child care centers is important as a solution for providing temporary care to children when they are entrusted. West Denpasar is one of the sub-districts in Denpasar City which has a high population growth rate in early childhood but with inadequate distribution of educational and day care facilities. Therefore, it is necessary to have educational facilities that are directly integrated with child care, making it easier for parents to entrust their children. By using an approach that is related to user behavior, the building design will pay more attention to the safety and comfort of users, especially children as the main users in this Children's Center.